Pengaruh Jumlah Industri Jumlah Penduduk dan Output Terhadap Penyerapan Tenaga Kerja Sektor Industri Kecil di Indonesia - Azizah Malta; Ariusni Ariusni (Universitas Negeri Padang, 2023)
This study aims to determine and analyze how the influence of the number of industries, the population and also the output value on the absorption of labor in the small industrial sector in Indonesia. This study uses secondary data sourced from data obtained from official institutions and related institutions or data that has been managed by a second party and published by relevant institutions in this study, such as BPS, Department of Industry, trade, and so onresearch variables are grouped into two parts, namely first, the independent variable in the form of the number of industries, the number of industries and the value of output. Second, the dependent variable in the form of employment. This study uses panel data regression analysis using the Random Effect Model (REM) method with a cross section of the number of industries, population, output values for the 2015-2020 period. The results of the study show that the number of industries and the number of residents have a positive and significant effect on the absorption of labor in the small industrial sector in Indonesia. while the output value also has a positive but not significant effect on employment in the small industrial sector in Indonesia.